Brown adipose tissue recruitment in a rodent model of severe burns. Issue 7 (November 2020) - Bhattarai, Nisha; Rontoyanni, Victoria G.; Ross, Evan; Ogunbileje, John O.; Murton, Andrew J.; Porter, Craig
Abstract: Background: Severe burns results in a prolonged hypermetabolic response. Brown adipose tissue (BAT), abundant in uncoupling protein 1 (UCP1), plays a key role in non-shivering thermogenesis. We set out to determine if BAT is recruited in response to severe burns. Methods: Male balb-c mice underwent scald burns on approximately 20–25% of their total body surface. BAT was harvested from the interscapular fat pad of sham and burned mice at 3 h, 24 h, 4 days, and 10 days after injury. High-resolution respirometry was used to determine mitochondrial respiratory function in BAT. BAT protein concentration, and mitochondrial enzyme activity were also determined. Results: Respiration increased in BAT of burned mice, peaking at 24 h after injury (after injury, P < 0.001). While UCP1 independent respiration was not significantly altered by burn, UCP1 dependent respiration increased >2-fold at 24 h after injury when compared to the 3 h and sham group ( P < 0.01). Normalized to citrate synthase activity, total uncoupled ( P < 0.05) and UCP1 dependent ( P < 0.01) respiration remained elevated at 24 h after injury. Conclusions: We show a time-dependent recruitment of rodent BAT in response to severe burns. Given recent reports that humans, including patients with severe burns, have functional BAT, these data support a role for BAT in the hypermetabolic response to severe burns.